2022
DOI: 10.1109/twc.2021.3093722
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Physical Layer Anonymous Communications: Sender Detection and Anonymous Precoding

Abstract: Areas in Communications (JSAC) Special Issue on "Integrated Sensing and Communications (ISAC)", and Academic Chair of the IEEE ComSoc ISAC Emerging Technology Initiative (ISAC-ETI). He has served as the organizer and Co-Chair for several workshops, special sessions and tutorials in flagship IEEE conferences. His research interests include ISAC, vehicular network and intelligent transportation, and mmWave communications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…The receiver first estimates the transmitted vector and constructs the hypotheses ŷ relying on all the possible candidates' channels. Finally, the hypothesis having the smallest Euclidean distance to the actual signal is declared as the real sender [11]. This Euclidean distance based detection relies on the disparity of the small-scale channel fading among the potential senders.…”
Section: Sender Detection Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…The receiver first estimates the transmitted vector and constructs the hypotheses ŷ relying on all the possible candidates' channels. Finally, the hypothesis having the smallest Euclidean distance to the actual signal is declared as the real sender [11]. This Euclidean distance based detection relies on the disparity of the small-scale channel fading among the potential senders.…”
Section: Sender Detection Strategymentioning
confidence: 99%
“…The above approach shows that, using the signal propagation model and knowledge of the channel, the receiver can determine who the sender is, in a fashion that is completely independent from the decryption at higher layers. In other words, although the transmitted data can be anonymously authenticated/encrypted at higher layers by the sender, the receiver is able to directly unveil the sender at the PHY [11]. To this end, the classical precoders are no longer anonymous in nature, allowing a leakage of the sender's identify at the PHY.…”
Section: Sender Detection Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the existing channel estimation techniques rely on the specific pilot matrix in grant-free communications, the constant pilot matrix may introduce serious security problems when an eavesdropper has the knowledge of the pilot information. In this context, the physical layer security draws lot of attention Wei et al (2022) Wei et al (2021b). Rachlin and Baron (2008) showed that the CS-based encryption does not achieve Shannon's definition of perfect secrecy, but a computationally unbounded adversary can easily infer that the correct sparse signal has been recovered.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, there is scope to jointly exploit the correlation among the channels and transmitted data, so that the multi-user interference is possible to make constructive at each receiver, termed as interference utilization (IE) precoding (Masouros and Alsusa, 2007). The concept of constructive interference (CI) has been applied for anonymous communications (Wei et al, 2021a), cognitive radio (Law and Masouros, 2018), large-scale MIMO Masouros, 2016, 2017b), constant envelope (Amadori and Masouros, 2017a;Liu et al, 2017), hybrid beamforming (Hegde et al, 2019), multicell coordination (Wei et al, 2020b), rate-splitting (Salem et al, 2019), physical layer security (Khandaker et al, 2019;Wei et al, 2020a;Wei and Masouros, 2020), directional modulation (Wei et al, 2021b), and integrated sensing and communication systems (Liu et al, 2018). In the following section, we briefly discuss the IE-based precoder design.…”
Section: Introductionmentioning
confidence: 99%